The Central Limit Theorem for mth-Order Nonhomogeneous Markov Information Source. (11th December 2013) - Huang, Huilin
Abstract : We prove a central limit theorem for m th-order nonhomogeneous Markov information source by using the martingale central limit theorem under the condition of convergence of transition probability matrices for nonhomogeneous Markov chain in Cesàro sense.